Cardio-STIC (spatio-temporal image correlation) as genetic ultrasound of fetal Down syndrome. (2nd November 2015) - Tongsong, Theera; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Traisrisilp, Kuntharee
Abstract: Objective : To evaluate efficacy of cardio-STIC in detection of fetal Down syndrome. Methods : Cardio-STIC volume datasets (VDS) were prospectively collected from women during 16–22 weeks, consisting of 40 VDS acquired from fetuses with Down syndrome and 400 VDS from normal fetuses. All VDS were blindly analyzed. Results : Between both groups, most dimensions were comparable but the right-sided dimensions were significantly greater in fetuses with Down syndrome. Interestingly, shortening fraction was also significantly higher in affected fetuses. Right-to-left disproportion and shortening fraction were used as cardiac markers as well as other eight structural markers to predict fetal Down syndrome. Tricuspid regurgitation had highest sensitivity (30%); followed by VSD (27.5%), right-to-left disproportion (20.0%), and echogenic intra-cardiac foci (EIF; 17.5%). If the test was considered positive in case of the presence of any cardiac marker, cardio-STIC had a detection rate of 72.5% and false-positive rate of 19.5%. Likelihood ratio of each marker for modifying priori risk was also provided. Conclusion : Cardio-STIC as genetic ultrasound for Down syndrome had a detection rate of about 70% and false-positive rate 20%. Cardio-STIC analysis can be helpful in estimation of fetal risk for Down syndrome and counseling when the prenatal diagnosis of the syndrome is made.